Synergistic effect on inhibiton efficiency of coconut husk fibre essence in controlling corrosion of mild steel in neutral medium - Sankar, A; Kumar, S Ananth; Rameshkumar, S (Bangladesh Journal of Scientific and Industrial Research, 2015)
The corrosion inhibition nature of coconut husk essence for the corrosion of mild steel in tank water (neutral medium) was investigated using weight loss, electrochemical impedance and Potentiodynamic Polarization methods. The results revealed that coconut husk essence acts as a corrosion inhibitor in well water. The inhibition efficiency increased with an increase in inhibitor concentration. The inhibition is attributed to adsorption of the inhibitor on the steel surface. DOI: http://dx.doi.org/10.3329/bjsir.v49i3.22133 Bangladesh J. Sci. Ind. Res. 49(3), 185-188, 2014